NOvation Forum II (2024): Reimagining Innovation for the Public Good - Equipe editorial, NOvation (NOvation — Critical Studies of Innovation, 2025)
In a world increasingly captivated by the allure of technology and rapid innovation, the II NOvation Forum, held in 4-6 September 2024 at the Federal University of Paraná (UFPR), in Curitiba (Brazil), stands as a critical and inspiring milestone. Under the theme «Reimagining Innovation for the Public Good», students, practitioners, and scholars from across the globe gathered to question the prevailing narratives of innovation and to explore alternative futures grounded in social justice, sustainability, and collective well-being. Full programme of the II Forum here: https://sites.google.com/view/novationforum/home-en-us?authuser=0.